THE EFFECTIVENESS OF USING WHATSAPP GROUP ON VOCABULARY MASTERY AMONG STUDENTS AT UPT SPF SMP NEGERI 40 MAKASSAR - Suhaefi, Mutia; Atmowardoyo, Haryanto; Muhayyang, Maemuna (Universitas Negeri Makassar, 2022)
This study aims to determine the effectiveness of using WhatsApp groups to improve students' vocabulary mastery. The method used was quantitative with a pre-experimental research design with a sample of 15 class VII.1 student using a cluster random sampling technique. In obtaining data, the researcher used pretest and posttest as instruments. The results of the data analysis showed that by using WhatsApp groups, students' vocabulary mastery increased. This is evidenced by the t-test value which is smaller than P (0.000 <0.05), which means that H0 in this study is rejected and H1 is accepted. So, it concluded that the use of WhatsApp group is effective in increasing the vocabulary mastery of class VII.1 student at UPT SPF SMP Negeri 40 Makassar.